Experimental investigation of underwater friction-stir welding of 5083 marine-grade aluminum alloy. (March 2016) - Kishta, Emad Eldin; Darras, Basil
Friction-stir welding has emerged as an effective technique for the challenging task of welding aluminum alloys. This article presents a detailed experimental study on underwater friction-stir welding of 5083 marine-grade aluminum alloy. The effects of submersion, rotational speed, and translational speed were investigated. The thermal histories, void fractions, microhardness, and tensile properties of the welded alloy samples, as well as power consumption of the process, were measured and analyzed. The results showed that underwater friction-stir welding produced good tensile properties and led to a significant reduction in the void fraction.